Sosialisasi Pemanfaatan Teknologi Internet of Things untuk Menjaga Sawah dari Serangan Hama Tikus - Trianto, Topan; Ridwana, Azkar Azkiya (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2023)
In the agricultural sector, especially rice fields, rat pest control is a serious challenge for farmers because of its negative impact on crop yields. This activity aims to provide knowledge to the public about the use of Internet of Things (IoT) technology so that people are aware and try to apply the technology to repel rat pests in rice fields. The method used in this activity is the PAR (Participatory Action Research) method. As a result of this activity, the community gained knowledge about IoT in order to reduce plant damage due to rat attacks.